Assessment of productive lifespan of dairy cattle using accelerated failure time models - V. L., Gleeja; Dhiya Paul; Syam Mohan; Rojan P. M (Indian Journal of Dairy Science, 2025)
Augmenting productivity and productive lifespan (PL) of dairy cow, to meet the increased demand of milk in Kerala needs identification of factors influencing PL of dairy cow and developing model to estimate the influence of different factors on PL. The PL of 205 cross breed cows which had first date of calving in between 2010 and 2018 and milked in University Livestock Farm and Fodder Research and Development Scheme (ULF & FRDS), College of Veterinary and Animal Sciences, Mannuthy was analysed using survival regression models. The median PL obtained was 1426 days (nearly three years eleven months). As per the results of the study, Age at first calving (AFC) had a significant and negative correlation with PL (p<0.05) whereas, first lactation yield had a positive and significant (p<0.05) correlation with PL. Analysis of various accelerated failure time models based on their accuracy measures revealed Weibull regression model with information on AFC as the appropriate model for predicting PL. Better PL were observed in cattle with AFC of two to 2.5 years. Hence, the study provides an optimum model for prediction of PL of dairy cattle and also depicts the importance of AFC in optimising PL of dairy cattle.